YAP/TAZ Regulate Elevation and Bone Formation of the Mouse Secondary Palate. (November 2020) - Goodwin, A.F.; Chen, C.P.; Vo, N.T.; Bush, J.O.; Klein, O.D.
Clefting of the secondary palate is one of the most common congenital anomalies, and the multiple corrective surgeries that individuals with isolated cleft palate undergo are associated with major costs and morbidities. Secondary palate development is a complex, multistep process that includes the elevation of the palatal shelves from a vertical to horizontal position, a process that is not well understood. The Hippo signaling cascade is a mechanosensory pathway that regulates morphogenesis, homeostasis, and regeneration by controlling cell proliferation, apoptosis, and differentiation, primarily via negative regulation of the downstream effectors, Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ). We deleted Yap / Taz throughout the palatal shelf mesenchyme as well as specifically in the posterior palatal shelf mesenchyme, using the Osr2 Cre and Col2 Cre drivers, respectively, which resulted in palatal shelf elevation delay and clefting of the secondary palate. In addition, the deletion resulted in undersized bones of the secondary palate. We next determined downstream targets of YAP/TAZ in the posterior palatal shelves, which included Ibsp and Phex, genes involved in mineralization, and Loxl4, which encodes a lysyl oxidase that catalyzes collagen crosslinking. Ibsp, Phex, and Loxl4 were expressed at decreased levels in the ossification region in the posterior palatal shelf mesenchyme upon deletion of Yap / Taz . Furthermore, collagen levels were decreased specifically in the same region prior to elevation. Thus, our data suggest that YAP/TAZ may regulate collagen crosslinking in the palatal shelf mesenchyme, thus controlling palatal shelf elevation, as well as mineralization of the bones of the secondary palate.